The changing face of the Mary Valley: considering the fairness, sustainability and resilience of the agricultural system in a peri-urban setting. Issue 5 (4th May 2017) - Singh-Peterson, Lila; Lawrence, Geoffrey
ABSTRACT: Agricultural systems around the world are being severely impacted by changing climate, extreme weather events, urbanisation and neo-liberal (free market) policies. Yet, there are currently few studies on the experiences of those affected by these compounding pressures captured at the local scale. Experiences of adaptive responses – along with recommendations for transformations of the agricultural systems provided by those working in local-level settings – have also not been captured. Yet, such responses provide valuable insights into what can be done, and what needs to be done, to bring about a more equitable and sustainable food system. In this paper, we draw upon the opinions and experiences of those involved in food production and distribution in the historically abundant, peri-urban, region of the Mary Valley, Queensland, Australia. Underpinning the practical and strategic recommendations made by participants is a need for supermarket and government policies to appropriately reflect the immense value of small-scale farmers in sustaining rural communities and enhancing the resilience and sustainability of Australia's food security. Importantly, our participants in this case study location reiterate that the impacts of climate change are manageable if the farming business is able to generate enough profit to absorb the costs of preparation and recovery from disasters.